Surface‐Driven Collagen Self‐Assembly Affects Early Osteogenic Stem Cell Signaling. Issue 12 (29th April 2016) - Razafiarison, Tojo; Silván, Unai; Meier, Daniela; Snedeker, Jess G.
Abstract : This study reports how extracellular matrix (ECM) ligand self‐assembly on biomaterial surfaces and the resulting nanoscale architecture can drive stem cell behavior. To isolate the biological effects of surface wettability on protein deposition, folding, and ligand activity, a polydimethylsiloxane (PDMS)‐based platform was developed and characterized with the ability to tune wettability of elastomeric substrates with otherwise equivalent topology, ligand loading, and mechanical properties. Using this platform, markedly different assembly of covalently bound type I collagen monomers was observed depending on wettability, with hydrophobic substrates yielding a relatively rough layer of collagen aggregates compared to a smooth collagen layer on more hydrophilic substrates. Cellular and molecular investigations with human bone marrow stromal cells revealed higher osteogenic differentiation and upregulation of focal adhesion‐related components on the resulting smooth collagen layer coated substrates. The initial collagen assembly driven by the PDMS surface directly affected α1β1 integrin/discoidin domain receptor 1 signaling, activation of the extracellular signal‐regulated kinase/mitogen activated protein kinase pathway, and ultimately markers of osteogenic stem cell differentiation. We demonstrate for the first time that surface‐driven ligand assembly on material surfaces, even on materials with otherwise identical starting topographies and mechanical properties, can dominate the biomaterial surface‐driven cell response. Abstract : The role of supramolecular ligand assembly on silicone substrates as a potential significant regulator of human bone marrow stromal cell adhesion and differentiation is investigated. A smooth collagen topography obtained on hydrophilic silicone tends to accelerate the onset of osteogenic differentiation when compared to the rough collagen layer on pristine hydrophobic silicone.